Guianensin, a Simulium guianense salivary protein, has broad anti-hemostatic and anti-inflammatory properties - Valenzuela-Leon, Paola Carolina; Campos Chagas, Andrezza; Martin-Martin, Ines; Williams, Adeline E.; Berger, Markus; Shrivastava, Gaurav; Paige, Andrew S.; Kotsyfakis, Michalis; Tirloni, Lucas; Calvo, Eric (Frontiers in Immunology, 2023)
Background Salivary glands from blood-feeding arthropods secrete several molecules that inhibit mammalian hemostasis and facilitate blood feeding and pathogen transmission. The salivary functions from Simulium guianense, the main vector of Onchocerciasis in South America, remain largely understudied. Here, we have characterized a salivary protease inhibitor (Guianensin) from the blackfly Simulium guianense. Materials and methods A combination of bioinformatic and biophysical analyses, recombinant protein production, in vitro and in vivo experiments were utilized to characterize the molecula mechanism of action of Guianensin. Kinetics of Guianensin interaction with proteases involved in vertebrate inflammation and coagulation were carried out by surface plasmon resonance and isothermal titration calorimetry. Plasma recalcification and coagulometry and tail bleeding assays were performed to understand the role of Guianensin in coagulation. Results Guianensin was identified in the sialotranscriptome of adult S. guianense flies and belongs to the Kunitz domain of protease inhibitors. It targets various serine proteases involved in hemostasis and inflammation. Binding to these enzymes is highly specific to the catalytic site and is not detectable for their zymogens, the catalytic site-blocked human coagulation factor Xa (FXa), or thrombin. Accordingly, Guianensin significantly increased both PT (Prothrombin time) and aPTT (Activated partial thromboplastin time) in human plasma and consequently increased blood clotting time ex vivo. Guianensin also inhibited prothrombinase activity on endothelial cells. We show that Guianensin acts as a potent anti-inflammatory molecule on FXa-induced paw edema formation in mice. Conclusion The information generated by this work highlights the biological functionality of Guianensin as an antithrombotic and anti-inflammatory protein that may play significant roles in blood feeding and pathogen transmission.